2018
DOI: 10.1063/1.5054008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of phase competition in terbium

Abstract: The competition among multiple solid phases determines the final microstructures of a material. Such competition can originate at the very beginning of the solidification process. We report the results of molecular dynamics simulation of the phase competition between the hexagonal close-packed (hcp), facecentered cubic (fcc), and body-centered cubic (bcc) phases during the solidification of pure Tb. We found that the liquid supercooled below the hcp melting temperature has both bcc and hcp/fcc nuclei, but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Interestingly, a similar crystallization mechanism was observed for pure Tb in Ref. 32. We also note that the fraction of the Z16 which is typical for the Laves phases is slightly higher in the liquid Cu 64.5 Zr 35.5 alloy described by the FS2 potential than that in the same liquid alloy described by the FS1 potential.…”
Section: Molecular Dynamics Simulation Of Solidification In Cu-zr Alloyssupporting
confidence: 85%
“…Interestingly, a similar crystallization mechanism was observed for pure Tb in Ref. 32. We also note that the fraction of the Z16 which is typical for the Laves phases is slightly higher in the liquid Cu 64.5 Zr 35.5 alloy described by the FS2 potential than that in the same liquid alloy described by the FS1 potential.…”
Section: Molecular Dynamics Simulation Of Solidification In Cu-zr Alloyssupporting
confidence: 85%
“…Therefore, instead of the single-pathway scenario, we can consider a complex process in which nucleation is facilitated by forming an intermediate phase with a high-nucleation rate. For example, it has been observed that the bcc phase can nucleate before the face-centered, cubic (fcc) or hcp phases in a few alloys in which the fcc/hcp phase is the most stable one ( 20 24 ). Could the bcc phase also facilitate hcp iron nucleation and relate to the inner core nucleation paradox?…”
mentioning
confidence: 99%
“…Instead of the scenario described above, where the melt in the Earth's core crystallized directly into the hcp phase, we can consider a complex process where nucleation is facilitated by forming a metastable phase with a high nucleation rate [17,18]. For example, it has been observed that the bcc phase can nucleate before facecentered cubic (fcc) or hcp phases in a few alloys where the fcc/hcp phase is the most stable one [19][20][21][22][23]. Could the bcc phase also facilitate hcp iron nucleation and relate to the inner core nucleation paradox?…”
mentioning
confidence: 99%